Comparison of Nutritional Status between Brahmin and Bote Children at Devghat Rural Municipality (Interdisciplinary Issues in Education, 2024)
This paper aims at comparing the nutritional status of Brahmin and Bote children. Descriptive design was used to garner and analyze the data collected from different sources. In this study, 25 children from the Brahmin community and 25 from the Bote community (altogether 50 children) and their mothers were selected as the sample by using the purposive sampling method. The study was especially based on primary sources of data. Data were collected by using an interview schedule and document analysis. This study depicted that the socio-economic and demographic status, knowledge, and attitude of Brahmin mothers towards nutrition were found quite better than Bote mothers. The practices of health behaviors regarding colostrum feeding, time of first pregnancy, frequency of breastfeeding, knowledge of preparing super flour, provision of additional food to children, and immunization practice in the Brahmin community were found quite good in the comparison of health behaviors that were found in Bote community. Most of the females from the Bote community faced early pregnancy than Brahmin females. In the Brahmin community, the majority of the mothers became pregnant for the first time at the age of 20 years and above. Similarly, in the Bote community, only 21.74 percent of mothers became pregnant at the age of 20 and above. Bote mothers were found less knowledgeable about the advantages of colostrum than the mothers who come from the Brahmin community.